2004
DOI: 10.1097/00005176-200411000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Sialic Acids in the Milk of Spanish Mothers of Full Term Infants During Lactation

Abstract: In human milk from Spanish women we observed slightly different values than those previously reported. This could be a result of population differences but nutritional or methodological aspects can not be discarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
3
35
1
Order By: Relevance
“…The content of total SA found in the analyzed HM (see Table 4) is close to that reported by Neeser et al (1991) for HM up to the fourth month of lactation, but lower than that published by Martín-Sosa et al (2004) on day 28e32 of lactation, and higher than that recorded by Carlson (1985) on day 20e28 of lactation (see Table 1). Recently, Wang (2009), in a general review on SA, pointed out great variability in the total SA contents in HM, related to genetic, geographic and dietetic factors of lactating mothers.…”
Section: Human Milksupporting
confidence: 79%
See 2 more Smart Citations
“…The content of total SA found in the analyzed HM (see Table 4) is close to that reported by Neeser et al (1991) for HM up to the fourth month of lactation, but lower than that published by Martín-Sosa et al (2004) on day 28e32 of lactation, and higher than that recorded by Carlson (1985) on day 20e28 of lactation (see Table 1). Recently, Wang (2009), in a general review on SA, pointed out great variability in the total SA contents in HM, related to genetic, geographic and dietetic factors of lactating mothers.…”
Section: Human Milksupporting
confidence: 79%
“…No data on specific forms of SA (Neu5Ac and Neu5Gc) in human milk (HM) have been found in the literature, and only a few studies have been made in the milk of other mammalian species (Puente & Hueso,1993;Spichtig, Michaud, & Austin, 2010;Tang, Liang, Cai, & Mou, 2008). In this context, gangliosides also decrease their content and change their profile: from 7.3 mg L À1 distributed as GD 3 (Neu5Aca2,8Neu5Aca2,3Galb1,4Glc-Cer) 70% and GM 3 (Neu5-Aca2,3Galb1,4Glc-Cer) 9% (colostrum) to 4.0 mg L À1 distributed as GD 3 9% and GM 3 85% (mature milk of 390 days of lactation) (Iwamori, Takamizawa, Momoeda, Iwamori, & Taketani, 2008;Martín-Sosa et al, 2004;Takamizawa, Iwamori, Mutai, & Nagai, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of sialylation is reported to be a general trend over lactation [27,28] and overlaps with the decrease of total as well as protein-bound sialic acid over lactation [28,29]. The high α1,6-fucosylation is a general feature for human milk glycoconjugates [25], and the α1,6-linked fucose was highly expressed on milk FN glycan (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 72%
“…A number of studies have reported ganglioside concentrations in HBM for different population groups, ranging from as low as 1.7 mg l -1 [8] to as high as 23.8 mg l -1 [9]. This variation in concentration has been attributed to differences among the various extraction and analytical methodologies used for measuring these gangliosides, population demographics, diet, time of sampling and study protocol [10][11][12].…”
Section: Introductionmentioning
confidence: 99%